THE EFFECTIVENESS OF THE FORUM KAMPUS UMKM KUNINGAN PROGRAM IN DEVELOPING MEMBERS’ ENTREPRENEURIAL CHARACTERISTICS AND COMPETENCIES - Dwi Lestari; Endang Sugiarti; Yayan Sudaryana; Mukrodi; Ruknan (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
This study evaluates the effectiveness of the Forum Kampus UMKM Kuningan program in fostering entrepreneurial characteristics and competencies among its members. As a community-based initiative, the forum strengthens local micro and small enterprises through training, mentoring, and peer learning. Employing a qualitative descriptive approach with the CIPP evaluation model, Bygrave’s 10D framework, and the KSA model, data were collected by interviews, observation, and documentation, then analyzed thematically. Findings indicate the program is generally effective: it addresses members’ real needs, engages competent facilitators despite limited resources, promotes participatory learning, and generates positive impacts on mindset, business practices, and networks. Key entrepreneurial traits—Dreams, Doers, and Destiny—showed significant growth, while financial literacy (Dollars) remained a challenge. Competencies improved across knowledge, practical and digital marketing skills, and attitudes such as confidence, discipline, and adaptability. Overall, the forum demonstrates effectiveness as a community-based entrepreneurship development model that strengthens the local MSME ecosystem.